IMPLEMENTASI PERENCANAAN PARTISIPATIF DALAM PEMBANGUNAN FISIK DI DESA SUCI KECAMATAN MUNDU KABUPATEN CIREBON - Nuril Rachmawati; Nurudin Siraj; RM Haryo Bharoto (Universitas Swadaya Gunung Jati, 2018)
ABSTRACT In village communities, participatory planning is a very important instrument. Because participatory planning which is one of the series of development trips mentioned above is the first stage that is crucial for the success of the development process, especially in the village.In the Holy Village Mundu District Cirebon District., there is a problem that is not yet fully visible in the implementation of participatory planning and optimization of its activities. Then it is generally found that during this time the level of community participation in development planning is lacking, In Suci village lack of public facilities and less optimal physical development in progress.This research was conducted with the aim to know the Implementation of Participatory Planning in Physical Development in the Holy Village Mundu District Cirebon District. The research method used is Qualilative research method. In this study, the author tries to describe the Implementation of Participatory Planning in Physical Development in the Holy Village Mundu District Cirebon District.The results of research on the implementation of participatory planning in physical development in the holy village of mundu district of Cirebon district are seen from the dimensions of communication gap, the material composed, the scope of the main idea of the implementation of activities, the role of the community, the detailed objectives in the planning, the motivation of community leaders, social gain legitimacy from community component which not yet fully optimal, need to be improved again participative planning until the end, due to lack of ideas channeled and busyness of citizen of Suci Village Mundu Sub-district of Cirebon Regency and other inhibiting factors. Therefore, efforts should be made in improving the level of participation in the Suci Village District Mundu Cirebon regency.